Antimicrobial resistance, Virulence profiles of Salmonella enterica serovar Typhimurium isolated from clinical samples - Hussain , Ezat (University of Thi-Qar Journal of Science, 2015)
A total of 33 Salmonella enterica serovar (ser.) Typhimurium isolates were isolated from clinical samples. Theseisolates were subjected to testing and analyzed for antibiotic resistance and virulence genes by using simplex PCR. All isolates were sensitive to gentamycin, kanamycin, nalidixic acid, chloramphenicol, and sulfisoxazol. on other hands the isolates showed intermediate resistance to streptomycin while one isolate (# 22) showed resistance to chloramphenicol and tetracycline. For ampicillin, six isolates were resistance to the drug. 33 of the showed either intermediate or full resistance to one or two of the animicrobials tested. Most isolates were positive for teen of the virulence genes tested (msgA, tolC, spaN, invA, ipfC, sitC,sopB, orgA, pagC and pefA ) . For sitC, three isolated were negative to this virulence gene .While two isolate were negative to lpfC . One isolate # 33 was negative to orgA and spaN. These results suggest that S. Typhimurium from clinical is virulent, and that capable of causing salmonellosis in humans and it may contribute to pathogenesis.